2020
DOI: 10.1590/1678-5150-pvb-6580
|View full text |Cite
|
Sign up to set email alerts
|

Avipoxvirus detected in tumor-like lesions in a white-faced whistling duck (Dendrocygna viduata)

Abstract: Avipoxvirus is the etiological agent of the avian pox, a well-known disease of captive and wild birds, and it has been associated with tumor-like lesions in some avian species. A white-faced whistling duck (Dendrocygna viduata) raised in captivity was referred to a Veterinary Teaching Hospital in Northeast due to cutaneous nodules present in both wings. A few days after the clinical examination, the animal died naturally. Once submitted to necropsy, histopathological evaluation of the lesions revealed clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Studies conducted in the Southeastern region of Brazil, the same area of the current research, have reported the presence of APV sequences clustered in subclade A1 and isolated from both turkeys and chickens 29 , 30 . Moreover, in the Northeastern region of Brazil, Braga et al 31 isolated APVs with lineage clustering in the A1 subclade coming from a Brazilian native duck ( Dendrocygna viduata ) (Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted in the Southeastern region of Brazil, the same area of the current research, have reported the presence of APV sequences clustered in subclade A1 and isolated from both turkeys and chickens 29 , 30 . Moreover, in the Northeastern region of Brazil, Braga et al 31 isolated APVs with lineage clustering in the A1 subclade coming from a Brazilian native duck ( Dendrocygna viduata ) (Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the lineages of APVs from subclade A1 were strongly associated with Galliform hosts ( Gallus gallus and Meleagris gallopavo ) according to the results published by Gyuranecz et al 20 , Jarmin et al 32 , and Manarolla et al 21 . Nevertheless, recent records of the APVs-A1 sequence infecting a Brazilian native duck (Order Anseriformes) reported by Braga et al 31 have raised questions about this subclade’s specificity within the species of the Galliformes order. Furthermore, given the fact that the most common APV host species of subclade A1 ( Gallus and Meleagris gallopavo ) are exotic species introduced by humans as food resources in most regions of the globe, such as in Brazil, it is possible to suggest that the lineages of APVs of the A1 subclade accompany their hosts in species introduction around the globe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cutaneous form of avian pox is mainly found in the unfeathered skin of birds, 1 and in ducks the cutaneous mass was seen in eyelids, beaks and legs in the humerus-radio-ulnar joint region of both wings. 27,28 Due to its distinctive clinical presentations, pox disease is remarkably simple to diagnose. However, gross and microscopic lesions, serology molecular techniques and electron microscopy can also be used to confirm the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the usual small dry scab or wart‐like lesion presentation of avian pox, a large nodular mass was seen on the leg of the examined duck gradually in other ducks from the same flock. The cutaneous form of avian pox is mainly found in the unfeathered skin of birds, 1 and in ducks the cutaneous mass was seen in eyelids, beaks and legs in the humerus‐radio‐ulnar joint region of both wings 27,28 …”
Section: Discussionmentioning
confidence: 99%